The effect of casting modulus in hypo-eutectic ductile iron unalloyed and alloyed with nickel on microstructure and mechanical properties (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The effect of the casting modulus on the distribution and features of graphite in hypo-eutectic ductile iron unalloyed and alloyed with nickel (0.88 wt %) was studied. The high cooling rate of the casting plates of 25.4, 12.7 and 8.5 mm in thickness with a casting modulus of 6.87, 4.46 and 3.31 mm, respectively promotes several microstructural changes, such as carbide precipitation and a noticeable nodule count increment. The nickel addition suppressed the carbides formation and improves the nodule count and nodularity for the three casting modulus evaluated. The nickel addition increases the nodule count in 69, 67 and 128 % for the modulus of 3.31, 4.46 and 6.87 mm, respectively regarding the unalloyed ductile iron. It was found that the biggest casting modulus produces the biggest nodules with the lowest nodule count for both ductile cast irons. Further to the improves in the graphite features, the nickel addition allowing to keep almost constant the yield and tensile strength ratio for the different casting modulus.